A Potential Role for Creatine in Drug Abuse? - D’Anci, Kristen E.; Allen, Patricia J.; Kanarek, Robin B. (Molecular neurobiology, 2011)
Supplemental creatine has been promoted for its positive health effects and is best known for its use by athletes to increase muscle mass. In addition to its role in physical performance, creatine supplementation has protective effects on the brain in models of neuronal damage and also alters mood state and cognitive performance. Creatine is found in high protein foods, such as fish or meat, and is also produced endogenously from the biosynthesis of arginine, glycine, and methionine. Changes in brain creatine levels, as measured using magnetic resonance spectroscopy, are seen in individuals exposed to drugs of abuse and depressed individuals. These changes in brain creatine indicate that energy metabolism differs in these populations relative to healthy individuals. Recent work shows that creatine supplementation has the ability to function in a manner similar to antidepressant drugs and can offset negative consequences of stress. These observations are important in relation to addictive behaviors as addiction is influenced by psychological factors such as psychosocial stress and depression. The significance of altered brain levels of creatine in drug-exposed individuals and the role of creatine supplementation in models of drug abuse have yet to be explored and represent gaps in the current understanding of brain energetics and addiction.